Comparative transcriptome and metabolome analysis of sweet potato (Ipomoea batatas (L.) Lam.) tuber development - Lin, Yanhui; Li, Yapeng; Zhu, Honglin; Tang, Liqiong; Xu, Jing (Frontiers in Plant Science, 2025)
IntroductionSweet potato is an important food, feed and industrial raw material, and its tubers are rich in starch, carotenoids and anthocyanins.MethodsTo elucidate the gene expression regulation and metabolic characteristics during the development of sweet potato tubers, transcriptomic and metabolomic analyses were performed on the tubers of three different sweet potato varieties at three developmental stages (70, 100, and 130 days (d)).ResultsRNA-seq analysis revealed that 16,303 differentially expressed genes (DEGs) were divided into 12 clusters according to their expression patterns, and the pathways of each cluster were annotated. A total of 9118 DEGs were divided into three categories during the same developmental period. A total of 1566 metabolites were detected, which were mainly divided into 12 categories. DEGs and differentially regulated metabolites (DRMs) were significantly enriched in the starch and sucrose metabolism and flavonoid biosynthesis pathways. The DEGs associated with the flavonoid pathway showed greater expression with the development of tubers, with the highest expression occurring at 130 d; chalcone isomerase (CHI) was a key gene associated with 11 flavonoid compounds. The DEGs associated with the starch pathway presented relatively low expression during the development of tubers, with the highest expression occurring at 70 d; UDP-glucose pyrophosphorylase 2 (UPG2) and glycogen synthase (glgA) were able to regulate the key genes of 8 metabolites related to the starch biosynthesis pathway. The anthocyanin content is directly related to changes in the content of peonidin-3-O-(6”-O-feruloyl)sophoroside-5-O-glucoside, which is regulated by the IbCHI gene. The abundance of this starch is directly related to changes in the content of D-glucose 6-phosphate and is regulated by the IbUGP2 and IbglgA genes. A total of 14 candidate genes related to starch, carotenoids and anthocyanins in sweet potato tubers, including the IbCHI, IbUGP2 and IbglgA genes, were identified via weighted correlation network analysis (WGCNA).ConclusionThis research provides fresh insights into the levels of anthocyanins, starch, and carotenoids throughout the growth of sweet potato tubers and sheds light on the potential regulatory pathways and candidate genes involved in this developmental progression.